О йотации в праславянском и балтийских языках - Николаевич Чекман, Валерий (Baltistica, 1975)
ON THE ΥΟΤΑTIΟΝ IN SLAVIC AND BALTICThe author shows that from the typological point of view the so-called "Balto-Slave palatalization" Ci̯V> С’V is impossible and there are no reasons to treat the evolution of the clusters Ci̯ in these languages as a common Balto-Slavic innovation.